NAMPT and NAPRT, Key Enzymes in NAD Salvage Synthesis Pathway, Are of Negative Prognostic Value in Colorectal Cancer - Li, Xiao-qin; Lei, Jing; Mao, Lin-hong; Wang, Qing-liang; Xu, Feng; Ran, Tao; Zhou, Zhi-hang; He, Song (Frontiers in Oncology, 2019)
Nicotinamide adenine dinucleotide (NAD) is a vital cofactor in redox reactions and a substrate for NAD consuming enzymes including CD38, PARPs and sirtuins. Nicotinamide phosphoribosyltransferase (NAMPT) and nicotinate phosphoribosyltransferase (NAPRT) are key enzymes for NAD salvage biosynthesis pathway, which is the main source of NAD. Few studies revealed that NAMPT and NAPRT reciprocally synthesize NAD, however, the prognostic value of NAMPT and NAPRT in colorectal cancer (CRC) remains largely unknown. Our present study detected NAMPT and NAPRT protein expression in cancer and adjacent tissues from 261 CRC. We showed that the high expression of NAMPT or NAPRT was associated with vascular invasion, invasion depth and advanced TNM stage. Both NAMPT and NAPRT are of negative prognostic value for CRC patients, which were confirmed by public databases. Moreover, NAMPT expression was positively correlated with NAPRT in CRC tissues and cell lines. NAPRThigh/NAMPThigh patients tended to have shortest overall survival and disease-free survival time. Finally, we revealed amplification, mutation, methylation, miRNA targets, and correlated pathways of NAMPT/NAPRT using public data. In conclusion, high expression of NAMPT and NAPRT predict poor prognosis of CRC patients, which might be novel targets for CRC intervention.